(untitled) (Research, Society and Development, 2020)
In this work, information on population structure, biometric, morphometric and density relationships are attributed as an indicator of the abundance of Colomesus psittacus and Sphoeroides testudineus, relating them to environmental variables, to verify possible interaction of the environment with the distribution of species. The collections were carried out from September 2012 to October 2013, using block-net gillnet. Analyzes of the averages (ANOVA, with an error of 5%) of total length (TL), weight (w) and abiotic variables were performed by different sources and statistical methods. Density, linear regression, sex ratio and size of first maturation (L50) were determined. 1,476 individuals, 1,367 C. psittacus and 109 S. testudineus were captured. The results were not significant when analyzing the number of individuals (N) by sex and total length (TL) by species. The relative frequencies of females and males were close to the expected 1: 1 for both species. The biometric and morphometric relationships had negative allometries, except for males of S. testudineus. The C. psittacus L50 was 14.72 cm. Evidently C. psittacus completes its entire life cycle in the estuary. However, S. testudineus demonstrated transitory habits within the estuary, being found abundantly in more saline months.